Optimalisasi Pemanfaatan Limbah Ternak Sebagai Pupuk Organik Dan Biogas di desa Branjang - Dewi, Christine Natalia; Darmaningsih, Arzunia Chalistica; Raafi Saputra, Adien Ar; Indra Murti, Siswati; Jundan Handhayani, Firstya (STMIK Royal, 2026)
Abstract: The cattle farming community in Branjang Village, Semarang Regency, faces a primary issue of livestock waste accumulation that has not been optimally managed. This condition results in environmental pollution, unpleasant odors, and increased dependency on chemical fertilizers and liquefied petroleum gas (LPG). The main constraints are limited knowledge, skills, and access to waste processing technology. This community service program aims to optimize the utilization of cattle waste as organic fertilizer and alternative energy through the implementation of the Sustainability Techno-Integrated Agrofarm model. The method employed involves a participatory approach through extension, training, consultation, and the application of the appropriate MetaCow technology as a household-scale biogas digester. Program success was evaluated using pre-test and post-test instruments, analyzed by n-gain and paired sample t-test to assess improvements in participants’ knowledge and skills. The results demonstrate a significant enhancement in the community’s ability to process waste into economically valuable organic fertilizer and biogas, while also strengthening the institutional capacity of Sanggar Tani as a center for sustainable agricultural technology learning. This program contributes to the achievement of the Sustainable Development Goals (SDGs), particularly in clean energy, sustainable production, and environmental preservation. Keywords: biogas; digester; livestock waste; organic fertilizer; sustainable agriculture Abstrak: Masyarakat peternak sapi di Desa Branjang, Kabupaten Semarang menghadapi permasalahan utama yakni penumpukan limbah ternak yang belum dikelola secara optimal. Hal ini berdampak pada pencemaran lingkungan, munculnya bau tidak sedap, serta meningkatnya ketergantungan akan pupuk kimia serta gas elpiji. Kendala atama adalah karena keterbatasan pengetahuan, keterampilan, serta akses terhadap teknologi pengolahan limbah. Program pengabdian masyarakat ini bertujuan mengoptimalkan pemanfaatan limbah ternak sapi sebagai pupuk organik dan energi alternatif melalui penerapan model Sustainability Techno-Integrated Agrofarm. Metode yang digunakan adalah pendekatan partisipatif melalui penyuluhan, pelatihan, konsultasi, dan penerapan teknologi tepat guna MetaCow sebagai digester biogas rumah tangga, serta evaluasi keberhasilan melalui pre-test dan post-test yang dianalisis melalui uji n-gain dan paired sample t-test untuk menilai peningkatan tingkat pemahaman serta keterampilan peserta. Hasil kegiatan menunjukkan adanya peningkatan signifikan kemampuan masyarakat dalam mengolah limbah menjadi pupuk organik dan biogas yang bernilai ekonomis serta memperkuat kelembagaan Sanggar Tani sebagai pusat pembelajaran teknologi pertanian berkelanjutan. Program ini berkontribusi pada tercapainya tujuan pembangunan berkelanjutan (SDGs) khususnya energi bersih, produksi berkelanjutan, dan pelestarian lingkungan. Kata kunci: biogas; digester; limbah ternak; pupuk organik; pertanian berkelanjutan